Naratīvs J. Ezeriņa un A. Eglīša novelēs - Gātere, Elīza (Latvijas Universitāte, 2020)
Bakalaura darba centrā tiek izvirzītas latviešu rakstnieku Jāņa Ezeriņa un Anšlava Eglīša noveles, kurās tiek pētīti divi naratīva pamatelementi – redzespunkts jeb stāstītājs un personāži. Bakalaura darbs tiek balstīts naratoloģijas teorijā. Pētījuma mērķis ir atklāt naratīva struktūras raksturīgākās iezīmes radītajā redzespunktā jeb stāstītājā un personāžos Jāņa Ezeriņa un Anšlava Eglīša noveļu krājumos. Pētījuma uzdevumi ir apkopot un atlasīt nozīmīgāko naratīva teorētiķu par naratoloģijas teoriju, analizēt stāstītāju un personāžus novelēs, un izdarīt secinājumus. Rezultāti atklāj naratīva principus kādus autori izmanto noveļu krājumos.

This Bachelor sets out the short stories by latvian authors Janis Ezerins un Anslavs Eglitis, where there are researched two basic narative elements– a point of view or narrator and characters. This bachelor's is based on naratology theory. The aim of the research is to reveal the characteristic features of the narative structure at the generated or the narrator and characters, in the short stories of Janis Ezerins and Anslavs Eglitis. The tasks of the study are to gather and select the most important narative theorist on naratology theory, analyze the narrator and characters in short stories, and draw conclusions. Results reveal narative principles used by authors in short stories. This Bachelor sets out the short stories by latvian authors Jānis Ezeriņš un Anšlavs Eglītis, where there are researched two basic narative elements– a point of view or narrator and characters. This bachelor's is based on naratology theory. The aim of the research is to reveal the characteristic features of the narative structure at the generated or the narrator and characters, in the short stories of Janis Ezerins and Anslavs Eglitis. The tasks of the study are to gather and select the most important narative theorist on naratology theory, analyze the narrator and characters in short stories, and draw conclusions. Results reveal narative principles used by authors in short stories.
The Narrative in Short Stories of J. Ezeriņš and A. Eglītis
Keywords: Filoloģija; Jānis Ezeriņš; Anšlavs Eglītis; novele; naratīvs; naratoloģija